The ISIS Model and its Influence Over Global Terrorism - Mahmut Cengiz; Kutluer Karademir; Huseyin Cinoglu (European Scientific Journal, ESJ, 2022)
Counter-terrorism efforts against jihadist groups have been challenging for law enforcement and the military because terrorist organizations constantly update their tactics and mimic the successful strategies of popular and influential groups, such as ISIS, that have developed a specific model for carrying out their destructive acts. ISIS created its terrorism model in 2014 and has used it to control territory, spread its ideology, create provincial branches in different regions, inspire lone actors, and generate revenue. Terrorism databases are full of incidents that involve ISISstyle tactics, targets, and affiliated groups that act as provincial branches of ISIS. This paper examines how ISIS developed its model, what components that model involves, and how the model has influenced not only jihadist groups but also right-wing extremists and drug cartels around the world. The study uses a mixed method of quantative and qualitative research, and the proposed ISIS Model is developed through a rigorous literature review.